Small Landscape Elements Double Connectivity in Highly Fragmented Areas of the Brazilian Atlantic Forest - Siqueira, Flávia Freire; de Carvalho, Dulcineia; Rhodes, Jonathan; Archibald, Carla L.; Rezende, Vanessa Leite; van den Berg, Eduardo (Frontiers in Ecology and Evolution, 2021)
The Atlantic Forest in Brazil is a biodiversity hotspot, yet its diverse ecosystems and species are becoming increasingly threatened by habitat loss and extreme habitat fragmentation. Most habitat patches of Atlantic Forest are dispersed across agricultural landscapes (e.g., grazing and cropping) in relatively small and isolated fragments (80% < 50ha). Forest fragments <1ha, scattered trees in pastures, tree lines on trenches and fences, and remnant riparian forest, collectively called here Small Landscape Elements (SLEs), are very common in this context. While these SLEs make up much of the Atlantic Forest footprint, very little is known about their role or impact on the persistence and conservation of species. In this study, we investigate the role of SLEs on landscape configuration, particularly their contribution towards landscape connectivity of individuals and genetic flow between larger forest fragments. We randomly selected 20 buffers of 707 hectares within a polygon of 411,670 hectares located in the south of Minas Gerais State, Brazil, comprising an area that was completely covered by forest in the past. The forest cover randomly varied among the buffers. The structural connectivity was measured as the probability of connectivity based on graph theory that is related to disperser movement between landscape knots (habitat patches). We used three estimated dispersal distances in the models: pollen disperser insect (50 m), low-mobility seed disperser bird (100 m), high-mobility seed disperser bird (760 m). The SLEs together increased the probability of connectivity by roughly 50%, for all model dispersers, if compared to a theoretical baseline landscape containing no SLEs. Of all SLEs, riparian forests contribute the most towards enhancing landscape connectivity. In these highly fragmented landscapes, such as the Atlantic Forest (>70 %), the position of SLEs within the landscapes was more important than their respective areas for connectivity. Although the landscapes were deeply fragmented, we showed that the presence of SLEs can increase connectivity and reduce further biodiversity loss in the Atlantic Forest.